Excavations at Portchester Castle Volume IV: Medieval, the Inner Bailey - Cunliffe, Barry (Reports of the Research Committee of the Society of Antiquaries of London, 1985)
This is an account of excavations at Portchester Castle which took place under Barry Cunliffe in 1961-72. The volume deals with alterations made to the Roman fort between 1066 and 1632, when a castle was constructed in its interior. This volume describes the structural sequence and dating of the buildings and defences of the inner bailey of the castle. Included are specialist reports on the documentary sources for building works, the building materials, and other finds, including pottery, small objects, and animal bones. A concluding chapter considers the castle in its regional setting.